Dynamic Common Agency - Dirk Bergemann; Juuso Valimaki (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1998)
We consider a general model of dynamic common agency with symmetric information. We focus on Markov perfect equilibria and characterize theequilibrium set for a refinement of the Markov perfect equilibria. Particular attention is given to the existence of a marginal contribution equilibrium where each principal receives her contribution to the coalition of agent and remaining principals. The structure of the intertemporal payoffs is analyzed in terms of the flow marginal contribution. As a by-product, new results for the static common agency game are obtained. The general characterization results are then applied to two dynamic bidding games for a common agent: (i ) multi-task allocation and (ii ) job matching under uncertainty.
Keywords: D81; D83; 330; Common agency; dynamic bidding; marginal contribution; markov perfect equilibrium; coalition-proof equilibrium; job matching; multi-task allocation